\(In vitro\) shoot multiplication and the content of huperzine a in in vitro cultured \(Huperzia serrata\) (Thunb. Ex Murray) Trevis plants - Thi Huong, Ho; Lan Anh, Le Thi; Duc Thanh, Nguyen; Thuy Linh, Ngo Thi; Huu Dat, Ton That; Bich Thuy, Le Thi (Academia Journal of Biology, 2022)
Huperzia serrata (Thunb. Ex Murray) Trevis belonging to the Lycopodiaceae family contains the main active ingredient Huperzine A (HupA), which is effective in the treatment of dementia. However, H. serrata in nature contains a low content of HupA. Additionally, this plant grows very slowly and is overexploited, thereby leading to the risk of extinction. In this study, we used the in vitro shoot of H. serrata to induce shoot multiplication by tissue culture method and quantify the content of HupA in the in vitro cultured plant by High-Performance Liquid Chromatography (HPLC). The suitable nutrient medium for inducing shoot multiplication was 1/4 MS medium supplemented with 1 mg/L of kinetin. In this medium, the shoot multiplication rate was as high as 77.33%, the number of shoots/shoot multiplication was 6.02, and the shoot height was 1.61 cm. Based on the HPLC method, the content of HupA in the in vitro cultured plant was 300 µg/g. The content of HupA in the cultured H. serrata in Vietnam is reported for the first time in our study. This study shows in vitro shoot multiplication is a promising method for propagating H. serrata and can produce the cultured H. serrata with a high content of HupA. These findings contribute to conserving and preserving the gene source of H. serrata species, and at the same time, enhancing the content of HupA in the cultured H. serrata.